On the mechanism of influence of carbon nanoparticle additives on high-temperature oxidation of diesel fuels - Pylyavsky, Volodymyr S.; Polunkin, Yevhen V.; Yevdokymenko, Vitalii O.; Kameneva, Tetyana M.; Haidai, Olha O.; Melnykova, Svitlana L.; Bogomolov, Yuriy I. (V.P. Kukhar Institute of Bioorganic Chemistry and Petrochemistry of the National Academy of Sciences of Ukraine, 2025)
The problem of increasing the energy efficiency of liquid motor fuels due to ultra-small amounts of nanoparticles is considered. The relationship between the completeness of fuel combustion in engines and the preliminary liquid-phase oxidation of hydrocarbons in atomized droplets is discussed. High-temperature oxidation at 150 °С with air oxygen of model diesel fuel components in a bubble-type reactor was carried out. The effect of carbon spheroidal nanoclusters on the dynamics of changes in the composition of the liquid phase during oxidation under the same conditions of n-decane and n-dodecane was studied by gas-liquid chromatography. It is shown that the effect of nanoparticles on the conversion of hydrocarbons in a liquid oxidate can vary depending on the proximity of the oxidation process temperature and the boiling point of the liquid. For high-boiling n-dodecane (216 °C) under oxidation conditions at 150 °C, the presence of nanoparticles in the solution slows down the change in the composition of the liquid oxidate. When oxidizing a more low-boiling n-decane (174 °C), nanocluster additives accelerate the reduction of the initial hydrocarbon content in the liquid mass. The obtained results are explained by the simultaneous interaction of hydrocarbon molecules with oxygen in the liquid-phase and gas-phase reaction regions. Carbon nanoclusters inhibit chain reactions of liquid-phase oxidation in the kinetic mode, but activate gas-phase oxidation by accelerating the diffusion stage. Acceleration of diffusion and evaporation of hydrocarbons from the liquid phase is explained by a change in the supramolecular structure of the solution under the influence of nanoparticles with a decrease in viscosity. It is shown that the non-monotonic nature of the change in the viscosity of n-decane from the content of nanoclusters in the solution correlates with the extreme non-monotonic dependence of the energy efficiency of diesel fuel on the concentration of such additives. A possible dependence between the duration of the stages of evaporation of low-boiling components from sprayed droplets and the completeness of combustion of mixed motor fuels is considered.